Assessing tobacco use in an African population: Serum and urine cotinine cut-offs from South Africa. (1st February 2019) - Ware, Lisa J.; Charlton, Karen; Kruger, Ruan; Breet, Yolandi; van Rooyen, Johannes; Huisman, Hugo; Botha, Shani; Uys, Aletta S.; Rennie, Kirsten L.; Naidoo, Nirmala; Kowal, Paul; Schutte, Aletta E.
Highlights: One in five adults in South Africa report using tobacco products. Specific thresholds for cotinine biomarkers are needed for African adults. Cotinine ≥15 ng/ml (serum) and ≥300 ng/ml (urine) perform best. Abstract: Background: Cotinine, a nicotine metabolite, is used to measure tobacco use and exposure, but recommended cut-offs to differentiate tobacco users from those exposed through the environment range from 3 to 58 ng/ml in serum, and 2.5 to 550 ng/ml in urine. Cut-offs may differ by ethnicity, sex and age. As data from adults in Africa are scarce, our aim was to evaluate cut-offs for serum and urine cotinine that best predict self-reported tobacco use in South African adults. Methods: Two datasets were explored: African-PREDICT (n = 941 black and white healthy young adults, 20–30 years, serum cotinine); and WHO SAGE Wave 2 (n = 604 adults, 18–102 years, urine cotinine). Population specific cut-offs (ROC analyses) were compared with published cut-offs and self-reported tobacco use. Results: Overall, 19% (293 of 1545) reported current tobacco use. The following cotinine cut-offs showed the highest sensitivity and specificity: serum ≥15 ng/ml in black and white men, and white women; serum ≥10 ng/ml in black women; urine ≥300 ng/ml for black, mixed ancestry, and older adults (50-plus years); urine ≥500 ng/ml for younger adults (18–49 years). Specificity was lower for urine than for serum cotinine. Conclusion: Our study suggests that a serum cotinine level of ≥15 ng/ml and a urine cotinine level of ≥300 ng/ml best distinguish current tobacco users from non-users generally in the South African adult population.